Effects of propolis intake on endurance exercise and molecular signaling related to inflammation and oxidative stress - Xu, Xiaoying; Hu, Bing; Qu, Xiaorong (Frontiers in Nutrition, 2025)
Honey bees extract sticky material from the exudates of different plants which transform afterwards to propolis. Propolis from several global locations has been shown to contain a wide variety of polyphenolic chemicals. Recent studies have revealed that propolis possesses antioxidant, anti-inflammatory, and immunomodulatory abilities. In laboratory animal studies, it has been demonstrated that propolis can enhance the functioning of the antioxidant defense system and decrease the activity of nuclear factor-kappa B. As a result, they can effectively alleviate the damage caused by exercise. One of the main flavonoids found in propolis, quercetin, has been demonstrated to enhance muscle mitochondrial biogenesis and exercise capacity. Propolis may aid athletes in preventing oxidative and inflammatory damage to their muscles during exercise and enhance their athletic performance. The goal of the current review was to evaluate how propolis consumption affected the molecular signaling associated with antioxidant/oxidant state, pro/anti-inflammatory cytokines, and anaerobic/aerobic endurance.